Comment: A Study of Underwriters' Experience with Unseasoned New Issue - Nelson, Edward A. (Journal of Financial and Quantitative Analysis, 1974)
The financial management area has come a long way since Fred Weston in 1954 (Journal of Finance) called for more research in and application of financial theory. Now, Neuberger and Hammond advance investment theory by empirical studies in an area which has received little direct attention. Their researching of new issues' price behavior provides application of observed facts to substantiate policy recommendations framed within a certain investment psychology structure.